Direct Ink Writing of a Preceramic Polymer and Fillers to Produce Hardystonite (Ca2ZnSi2O7) Bioceramic Scaffolds. Issue 6 (22nd March 2016) - Zocca, Andrea; Franchin, Giorgia; Elsayed, Hamada; Gioffredi, Emilia; Bernardo, Enrico; Colombo, Paolo
Abstract : The direct ink writing of an ink composed of a preceramic polymer and fillers was used to produce hardystonite (Ca2 ZnSi2 O7 ) bioceramic scaffolds. Suitable formulations were developed for the extrusion of fine filaments (350 μm diameter) through a nozzle. The preceramic polymer was employed with the double purpose of contributing to the rheology of the ink by increasing its viscosity and of forming the hardystonite phase upon heat treatment by reacting with the fillers. A control of the rheology is essential when spanning features have to be produced, and therefore the main rheological characteristics of the inks were measured (flow curves, dynamic oscillation tests, viscosity recovery tests) and compared to models reported in the literature. Highly porous scaffolds (up to 80% total porosity) were produced and heat treated in air or in nitrogen atmosphere. The influence of the heat‐treatment atmosphere on the morphology, crystalline phase assemblage, and compressive strength of the scaffolds was investigated.